Regulation and Firm Value: Curious Case of Transparency and Disclosure Laws in Russia - Suman Banerjee; Ronald Masulis; Sarmistha Pal (Institute for the Study of Labor (IZA), 2016)
We provide novel evidence on the effectiveness of mandated changes in Russian transparency and disclosure (henceforth T&D) rules in boosting shareholder welfare. We focus on the staggered implementation of these T&D reforms initiated in 2002 and implemented during 2003-07. Using difference in difference method, we find that the reforms improved earnings quality, which on average reduced the operating performance (i.e., EBIT/Assets) of treated domestically-listed (relative to our control group of cross-listed) Russian firms, but had no significant impact on their market valuation. We argue that low tax alignment, where financial statements are not used for tax purposes, made it possible for managers of domestically-listed firms to inflate pre-reforms earnings, which became difficult post-reforms, leading to a drop in operating earnings. Yet, firm values, on average, remained unchanged because the drop in earnings was roughly offset by a decrease in the required market return due to more reliable accounting information post reform. Also, T&D reforms had negligible effects on cross-listed firms that act as our control group. Further, for domestically listed firms without a domestic controlling shareholder, post-reform reported earnings did not drop, while firm value increased significantly. For the domestically listed firms with a controlling shareholder, just the opposite occurred. Thus, a key finding of our study is that a strong governance structure is a prerequisite for significant gains in shareholder wealth following improved reliability of firm accounting information.
Keywords: G3; K2; P2; 330; transparency and disclosure rules; quasi-experimental analysis; domestic vs. cross-listed firms; firm performance; Tobin's Q; EBIT-to-Asset ratio; difference-in-difference method; Russia